Forum Size and Content Contribution per Person: A Field Experiment - Baek, Jiye; Shore, Jesse (Management Science, 2020)
Promoting contribution of content is a key challenge for platforms that support the collective creation or transfer of knowledge. We use a field experiment on a massive open online course to study the role of forum size (number of people in a forum) in the contribution of content per person. We find that larger forums elicit more contributions per person. The number of questions and other help-seeking threads posted per person was unchanged by forum size, but replies and other more conversational posts increased sharply. Most of the positive effect of size was in a subset of socially responsive subjects. The implication of social responsiveness driving our results is that the unequal distribution of contribution in online platforms is unlikely to be easily changed: if more contributions are elicited from infrequent contributors, the greatest contributors would contribute even more because there would be more to respond to. This paper was accepted by Chris Forman, information systems.